Community Involvement in Spatial Planning: A Study of Public Participation in Lerep Tourism Village Perspective of Indonesian Spatial Planning Law - Aprila Niravita; Rofi Wahanisa; Suhadi Suhadi; Rahayu Fery Anitasari; Bayangsari Wedhatami (Universitas Negeri Semarang, 2021)
Lerep village is one of the villages which is promoted as a tourism village according to Regent Decree No. 556/0424/2015 on the Establishment of a Tourism Village in Semarang Regency. The implementation is encouraged by Regulation of Lerep Village No. 4/2015 on the 2016 Working Plan of the Village Government. The development of a village as a tourism village brings positive and negative impacts. The positive impact is that the village can be more advanced and developed by utilizing its natural and cultural potential. The negative impact arising is that there is a significant development of the tourism locations, especially from outside parties. The negative impact that concerns society greatly is the allegation of irregularities or violation of spatial planning. The development will be carried out thoroughly to realize Lerep as a tourism village in terms of its human resources and the infrastructure supporting the tourism activities. The infrastructure development must be well-planned and able to optimize space use. The spatial planning must be able to provide safe, comfortable, productive, and sustainable space for all stakeholders. The realization of spatial planning is carried out by the central and regional governments by involving the society. Society plays a role in controlling space use based on functions and planning in order to realize Lerep tourism village which has awareness of spatial planning.